Six canonical projects by Rem Koolhaas : essays on the history of ideas - Böck, Ingrid; Koolhaas, Rem (Jovis, 2015)
Dutch architect, architectural theorist and urban thinker Rem Koolhaas (born 1944) has been a protagonist of the international architectural avant-garde since the 1970s; his numerous worldwide awards include the Pritzker Prize in 2000 for his lifetime achievement. Through a series of essays, this book interprets his many buildings and projects by drawing on Koolhaas' own theoretical oeuvre of polemics, manifestos, interviews, books such as Delirious New York and his so-called "design patents." In these writings, Koolhaas articulates a design method that links theory and practice, which this book not only orients within architectural history, but also shows how it repositions the function of the authors or the architects themselves. Rem Koolhaas (geb. 1944) zählt seit den 1970er Jahren zur internationalen Architektur-Avantgarde und wurde neben zahlreichen weltweiten Auszeichnungen im Jahr 2000 mit dem Pritzker-Preis für sein Lebenswerk geehrt. Im vorliegenden Buch werden erstmals Koolhaas’ zahlreiche Bauten und Projekte mithilfe seines umfangreichen theoretischen Werks interpretiert, das sich aus Polemiken, Manifesten, kulturwissenschaftlichen Büchern wie Delirious New York und sogenannten Entwurfspatenten zusammensetzt. Zwischen Theorie und Praxis hat Koolhaas eine evolutionäre Entwurfsmethode entwickelt, die der Band nicht nur mit dem Architekturwissen und der Ideengeschichte der Konzepte verbindet, sondern auch die Funktion des Autors/Architekten – und seine Originalität – im aktuellen Diskurs neu interpretiert.